2023
DOI: 10.1111/wvn.12645
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary investment in evidence‐based practice by chief nurses and stronger EBP cultures are associated with less turnover and better patient outcomes

Abstract: Background Hospitals and healthcare systems strive to meet benchmarks for the National Database of Nursing Quality Indicator (NDNQI) measures, Centers for Medicare & Medicaid Services (CMS) Core Measures, and Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) outcome indicators. Prior research indicates that Chief Nursing Officers and Executives (CNOs, CNEs) believe that evidence‐based practice (EBP) is important for ensuring the quality of care, but they allocate little funding to its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…These considerations informed by MMCS may have useful implications for implementation strategy selection and tailoring for future CCM implementation efforts, especially in delineating the target level (e.g., system, organizational, clinic, individual) and timeline of implementation strategies to be deployed. For instance, of the three factors found to most notably trend with CCM sustainability, Collaborativeness and teamwork may be strengthened through shorter-term team-building interventions at the organizational and/or clinic levels [ 38 ], Turnover of clinic staff and leadership may be mitigated by aiming for longer-term culture/climate change at the system and/or organizational levels [ 44 46 ], and Having a consistent and strong internal facilitator may be ensured more immediately by selecting an individual with fitting expertise/characteristics to serve in the role [ 15 ] and imparting innovation/facilitation knowledge to them [ 47 ]. Which of these factors to focus on, and through what specific strategies, can be decided in partnership with an implementation site—for instance, candidate strategies can be identified based on ones that literature points to for addressing these factors [ 48 ], systematic selection of the strategies to move forward can happen with close input from site personnel [ 49 ], and explicit further specification of those strategies [ 50 ] can also happen in collaboration with site personnel to amply account for site-specific contexts [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These considerations informed by MMCS may have useful implications for implementation strategy selection and tailoring for future CCM implementation efforts, especially in delineating the target level (e.g., system, organizational, clinic, individual) and timeline of implementation strategies to be deployed. For instance, of the three factors found to most notably trend with CCM sustainability, Collaborativeness and teamwork may be strengthened through shorter-term team-building interventions at the organizational and/or clinic levels [ 38 ], Turnover of clinic staff and leadership may be mitigated by aiming for longer-term culture/climate change at the system and/or organizational levels [ 44 46 ], and Having a consistent and strong internal facilitator may be ensured more immediately by selecting an individual with fitting expertise/characteristics to serve in the role [ 15 ] and imparting innovation/facilitation knowledge to them [ 47 ]. Which of these factors to focus on, and through what specific strategies, can be decided in partnership with an implementation site—for instance, candidate strategies can be identified based on ones that literature points to for addressing these factors [ 48 ], systematic selection of the strategies to move forward can happen with close input from site personnel [ 49 ], and explicit further specification of those strategies [ 50 ] can also happen in collaboration with site personnel to amply account for site-specific contexts [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Magnet organizations may need to dedicate more resources to prepare nurses to become highly competent in EBP to implement best practices consistently and improve patient outcomes. In a recent national study, it was found that one-third of chief nurses did not allocate any of the nursing budgets to EBP, and another 3rd allocated only 1% to 4% of their budgets to EBP 14 . However, hospitals that allocated more of their budgets to EBP had fewer patient falls and trauma, less nursing turnover, and stronger EBP cultures and other positive EBP attributes.…”
Section: Discussionmentioning
confidence: 99%
“…5 Nurse-led quality improvement initiatives thrive in this environment, yet most A-P partnerships have not been directly research-oriented or full partnerships, which may have impacted the use of EBP. 2 Melnyk and colleagues 6 report that the number of EBP projects increased when more EBP mentors were available.…”
Section: Introductionmentioning
confidence: 99%